PERLINDUNGAN DATA PRIBADI SEBAGAI BAGIAN DARI HAK ASASI MANUSIA ATAS PERLINDUNGAN DIRI PRIBADI - Upik Mutiara; Romi Maulana (Indonesian Journal of Law and Policy Studies, 2020)
Protection of personal data as closely related to the protection of personal and private rights. Indonesia does not yet have legislation that specifically regulates the protection of personal data. then the problem that the author raises is: the comparison of the right to personal protection as part of human rights in Indonesia with the constitution in other countries and the concept of comparing the protection of personal data as a manifestation of the human rights of personal protection in Indonesia and other countries. related to the protection of personal rights in Indonesia is a state constitutional obligation regulated in the 1945 Constitution of the Republic of Indonesia Article 28G Paragraph (1). The constitutions of other countries such as in several Asian, African, and European countries as mentioned above have explicitly regulated and mentioned the protection of guarantees and personal rights or privacy rights of their citizens. while in Indonesia such as Saudi Arabia and Madagascar it does not explicitly mention anything about the right of privacy in their constitution. it can be concluded that the concept of personal data protection can be found in international and regional instruments such as the European Union Data Protection Directive, the European Union Data Protection Convention, and the OECD Guidelines.